2021
DOI: 10.1242/dmm.048997
|View full text |Cite
|
Sign up to set email alerts
|

Loss of vacuolar-type H+-ATPase induces caspase-independent necrosis-like death of hair cells in zebrafish neuromasts

Abstract: The vacuolar type H+-ATPase (V-ATPase) is a ubiquitous membrane-bound, multi-subunit proton pump that regulates pH of cellular compartments. V-ATPase activity is known to modulate several cellular processes, but cell type-specific V-ATPase functions remain poorly understood. Patients with mutations in specific V-ATPase subunits can develop sensorineural deafness, but underlying mechanisms are unclear. Here, we show that V-ATPase mutations disrupt formation of zebrafish neuromasts, which serve as a model system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 137 publications
1
2
0
Order By: Relevance
“…To do this fish were treated with RU360 at 500nM from 3-5 dpf and then fish were fixed and hair cells were labeled for counting. Similar to what had previously been found with extended RU360 treatment (Santra & Amack, 2021) we found a significant decrease in the number of hair cells in wild-type siblings. However, we saw no changes in hair cell number in either IFT gene mutant following RU360 treatment (Figure 4).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…To do this fish were treated with RU360 at 500nM from 3-5 dpf and then fish were fixed and hair cells were labeled for counting. Similar to what had previously been found with extended RU360 treatment (Santra & Amack, 2021) we found a significant decrease in the number of hair cells in wild-type siblings. However, we saw no changes in hair cell number in either IFT gene mutant following RU360 treatment (Figure 4).…”
Section: Resultssupporting
confidence: 91%
“…In other hair cell mutants with reduced hair cell number and mitochondrial membrane potential decreases it has been shown that treatment with the mitochondrial calcium uniporter inhibitor RU360 can partially rescue decreases in hair cell number (Santra & Amack, 2021). We wished to test if this was true for IFT gene mutants.…”
Section: Mitochondria Dysfunction May Play a Role In Hair Cell Apopto...mentioning
confidence: 99%
“…Fluorescent immunostaining was performed as previously described ( Santra and Amack, 2021 ). Embryos were fixed in 4% paraformaldehyde +1% tween-20 in 1X phosphate-buffered saline (PBS) overnight at 4°C, and then dechorionated and permeabilized in 100% acetone at −20°C for 8 min.…”
Section: Methodsmentioning
confidence: 99%